2020
DOI: 10.3390/brainsci10060360
|View full text |Cite
|
Sign up to set email alerts
|

Migraine Frequency Decrease Following Prolonged Medical Cannabis Treatment: A Cross-Sectional Study

Abstract: Background: Medical cannabis (MC) treatment for migraine is practically emerging, although sufficient clinical data are not available for this indication. This cross-sectional questionnaire-based study aimed to investigate the associations between phytocannabinoid treatment and migraine frequency. Methods: Participants were migraine patients licensed for MC treatment. Data included self-reported questionnaires and MC treatment features. Patients were retrospectively classified as responders vs. non-responders … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 41 publications
(71 reference statements)
3
23
0
Order By: Relevance
“…Several studies have reported both the benefits and effectiveness of medical cannabis use. A prospective clinical trial done in 2020 by Aviram et al focused on 68 patients who smoked or vaped MC inflorescences evaluated the differences in total MC monthly dose between responders and non‐responders [ 17 ]. This study focused on the associations between phytocannabinoid treatment and migraine frequency [ 17 ].…”
Section: Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Several studies have reported both the benefits and effectiveness of medical cannabis use. A prospective clinical trial done in 2020 by Aviram et al focused on 68 patients who smoked or vaped MC inflorescences evaluated the differences in total MC monthly dose between responders and non‐responders [ 17 ]. This study focused on the associations between phytocannabinoid treatment and migraine frequency [ 17 ].…”
Section: Reviewmentioning
confidence: 99%
“…A prospective clinical trial done in 2020 by Aviram et al focused on 68 patients who smoked or vaped MC inflorescences evaluated the differences in total MC monthly dose between responders and non‐responders [ 17 ]. This study focused on the associations between phytocannabinoid treatment and migraine frequency [ 17 ]. The study also reported better migraine symptom reduction, less negative headache impact, better sleep quality, and decreased medication consumption [ 17 ].…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on treatment response, indexed as a decrease in monthly migraine attacks frequency ≥50%, authors were able to identify a specific strain with potential benefits, containing higher doses of the phytocannabinoid ms_373_15c and lower doses of the phytocannabinoid ms_331_18d. As stated by the authors themselves, the anti-migraine effect of such phytocannabinoids and whether they are biological active will have to be elucidated in future studies [ 22 ]. This Special Issue also hosts the study protocol of a randomized controlled trial aiming to evaluate the efficacy of adjunctive dronabinol (licensed form of ∆9-THC) at the doses of 5 to 30 mg/die versus control (systemic analgesics only) for reducing opioid consumption in adults aged 18–65 years with traumatic injury [ 23 ].…”
mentioning
confidence: 99%